Promoção da tutela jurisdicional coletiva no estado do Tocantins análise dos legitimados - Dangelo, Paula Guimarães (Universidade Federal do Tocantins, 2021)
This article aims to analyze the performance of the Public Ministry and Public Defender of the State of Tocantins in promoting collective consumer protection in 2018. It was collected data from the Justice in Numbers report, from the National Consumer Protection Information System and other reports. A comparison was made between the number of individual and collective actions filed that year and the results were inserted in a table, to conclude that the number of individual consumer actions grows every year, filling the Judiciary with similar causes that could be resolved promptly and collectively through Public Civil Action. This instrument enables judicial relief and guarantees access to justice effectively and comprehensively.